Demographic and disease patterns at a primary healthcare setting (Bangladesh Journal of Psychiatry, 2020)
Universal health coverage (UHC) implied that all people had access to quality health services they need, without financial hardship. Nandail had a population of 402,727 with high poverty and low literacy rate. The vast diversity of diseases presenting on daily basis to this facility needs to be quantified on the basis of age and gender and presenting symptoms of the diseases and organ systems involved. This study was aimed to determine the demographic characteristics and disease patterns related to different organ systems presenting at a union sub center. Proportion of smoking among these patients as well as their relation to disease patterns was also assessed. This was a cross-sectional study conducted using the union sub centers patient registry database retrospectively in order to determine the distribution and burden of various common diseases. Secondary data from patient register that presented for the first time and of those whom a specific diagnosis was possible were included into this study for a period of 21st February 2020 to 20th February 2021 were obtained. Any patient with vague symptoms, inconclusive diagnosis, repeated visits for similar symptoms/diseases were excluded from the study. The results showed that, out of total 1304 patients, 482 (37%) were males and 822 (63%) were females. Most of the patients 670 (51.3%) belonged to the age group of 15-49 years. The maximum patients 246 (18.9%) presented with symptoms involving musculoskeletal system. Certain systems like musculoskeletal system; neurology and endocrine were significantly more involved in females than males. Respiratory cases were seen more in males as compared to females. About 41% of male were smokers, highest smoking proportion was among those who aged 50 or more years. Those man who smoked had more chronic obstructive pulmonary disease (COPD), hypertension and peptic ulcer disease than those who didn’t. This study could act as landmark for future such studies which will ensure equitable distribution of limited resources and overall achieving greater efficacy.Bang J Psychiatry 2020; 34(2): 25-29